Contabilidade ambiental: um estudo do disclosure de informações ambientais, das empresas dos setores de alto impacto ambiental, integrantes do ISE Índice de Sustentabilidade Empresarial - Godoi, Alexandre Franco de (2011)
Environmental Accounting aims to provide adequate information of the measurement of economic events related to the environment by contributing to the disclosure of the decision making process of internal and external users. The search for greater disclosure and accountability of environmental issues has led companies to promote the dissemination of information in its financial statements, although not complying with any specific regulations. In Brazil, the environmental disclosure is not required by law or regulation, there are only guidelines that encourage their development. This research aims to analyze the characteristics of environmental disclosure in financial statements of a sample of companies of the Corporate Sustainability Index (CSI) Stock Exchange São Paulo (BOVESPA) and belonging to the economic sectors of high environmental impact. To achieve the goal we carried out a descriptive survey, relying on the theoretical foundation for literature and content analysis to analyze the environmental disclosure in the Financial Statements (DFP's) for the fiscal year 2009. The results indicate that because there is no legal requirement in Brazil companies opt to make the voluntary disclosure, with the features for this type of disclosure the predominance of environmental declarative sentences and good information for the image or some kind of credit for the company, are using the Management Report as the primary means for communication, which is not subject to verification by an auditor may be questioned about the credibility of the information it disclosed